INFLUENCE ANALYSIS OF PSYCHOGRAPHIC FACTORS ON CONSUMER PURCHASING DECISION IN MCDONALD’S MANADO - Lowongan, Esty Nindy (Sam Ratulangi University, 2015)
ABSTRACT The research aims to examine and analyze the influence of psychographic factors on consumer purchasing decision in McDonald’s Manado. Data is collected through distribution of questionnaires and implemented to 70 respondent in McDonald’s Manado. The data analysis in this research is using SPSS version 22. The sampling technique uses a nonprobability sampling method and the data testing technique is used within the research includes validity test by factor analysis, reliability test with cronbach. Classical assumption test and multiple linear regression analysis had used to verify and to prove the research hypothesis. The Analysis result demonstrates that lifestyle, personality, and demographic have positive influence on purchasing decision to consumer in McDonald’s Manado Keywords: Purchase Decision, lifestyle, Personality, and Demographic.